Formulation and Evaluation of Paracetamol and Diclofenac Sodium Bilayer Tablet as per QBD Approach - Tanwar, Abhishek; Billore, Sourabh; Patil, Ashwini; Arora, Khushboo; Khambete, Hemant; Jain, Sanjay (Journal of Neonatal Surgery, 2025)
The paper intends to enlighten the readers about the challenges of making dual-layer tablets and some possible solutions. In an effort to improve patient convenience and effectiveness, pharmaceutical companies over the years have been concentrating on blending multiple APIs in one drug as well as scrutinizing studies on the deployment of quality by design (Qbd) concepts in paracetamol and diclofenac sodium bilayered tablet formulation. This ranges from appraisal of critical material attributes (CMA) and critical process parameters (CPP) concerning critical quality attributes (CQA) in the process and finished product of the bilayer tablet. In order to control the drug release and maintain its concentration, the recent study deals with formulation and evaluation of bilayer tablet of Paracetamol and Diclofenac Sodium. By using a wet granulation process, the primary ingredients for both Diclofenac sodium and Paracetamol granules were made. Wet mass passed through sieve no. 10 while dry granules passed through sieve no. 22. Their percent friability, hardness, thickness, disintegration and in vitro drug release were evaluated after their preparation as bilayer tablets. Paracetamol showed 86.18% drug release while diclofenac sodium released 51.27% drugs.